Cloning and Expression of SCAMP3 in Escherichia coli BL21(DE3) with In Silico Sequence-Based Cancer Epitopes Prediction - Rajagukguk, Selly Setiati; Pambudi, Sabar; Dwiranti, Astari; Utomo, Doddy Irawan Setyo; Bowolaksono, Anom (UI Scholars Hub, 2025)
Secretory carrier membrane protein 3 (SCAMP3) is a crucial membrane protein involved in intracellular vesicle traffick-ing and exocytosis. The SCAMP3 expression has been observed in diverse cancer types, such as melanoma, glioma, hepatocellular and breast cancer. Increased SCAMP3 expression has been reported in certain cancer cells relative to that in normal cells, suggesting the potential role of SCAMP3 in cancer development or progression. In this study, we successfully cloned and expressed SCAMP3 in Escherichia coli strain BL21(DE3). SCAMP3 was amplified and insert-ed directionally into the prokaryotic expression vector pET21d(+). The transformation of recombinant plasmid into E. coli BL21(DE3) cells were performed for the protein expression. SDS–PAGE and Western blotting were performed to detect the expression product induced by IPTG, which confirmed the presence of a recombinant pET21d(+)-SCAMP3 at 38-kDa protein weight. Bioinformatics analyses helped discover several possible epitopes distributed throughout the SCAMP3 protein sequence. These findings together serve as a basis for future biochemical and functional studies on this important membrane protein alongside immunotherapy research related to SCAMP3 as a cancer biomarker.